(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to evaluate the outcomes of STLA for acute appendicitis in pediatric patients at Thai Nguyen National Hospital. Methods: A descriptive cross-sectional study was conducted on 52 pediatric patients who underwent STLA for acute appendicitis at the Pediatric Surgery Department, Thai Nguyen National Hospital, from July 2024 to June 2025. Clinical characteristics, intraoperative findings, and postoperative outcomes were analyzed. Results: The study included 52 children under 16 years old (29 boys, 23 girls; mean age 7.7 ± 2.3 years). Intraoperatively, 34 cases were diagnosed with catarrhal appendicitis and 18 cases with suppurative appendicitis. The mean operative time was 39.23 ± 6.14 minutes. The postoperative mean time to first flatus was 17.85 ± 5.52 hours, and the mean length of hospital stay was 5.65 ± 1.06 days. Postoperative complications occurred in 6 patients (11.5%), all of which were minor. No conversion to another surgical approach was required. Conclusion: Single-trocar laparoscopic appendectomy is an effective, safe, and minimally invasive technique with favorable short-term outcomes for children with uncomplicated acute appendicitis.